Gedung Pusat Pelayanan Keselamatan Terpadu Di Kota Palu Dengan Pendekatan Konsep Bentuk Yang Respon Terhadap Bencana Gempa - Hidayat S., M. Kurniawan; Arifin, R.; Salenda, H.; Basri, I. Setiawan (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2024)
For the effectiveness and smoothness in handling disasters and emergencies in the city of Palu, it is deemed necessary to have a Public Safety Center building that will facilitate disaster mitigation activities and serve as a first aid station in emergencies caused by disasters and accidents. According to the Regulation of the Minister of Health of the Republic of Indonesia Number 19 of 2016, the Public Safety Center (PSC) is a service center that guarantees the community's needs in matters related to emergencies within the district/city. Furthermore, because this building serves as a safety center, the design will incorporate a form concept approach that responds to earthquake disasters. This research is a study that uses the architectural design method. The architectural design method is a design process that will produce a design based on data collected beforehand, where the data is highly relevant to the research. The data were obtained through interviews, surveys, and field observations. The design concept of the building form for the Integrated Safety Service Center was created with a basic square shape. This shape was chosen with the consideration of aligning with the building's function, thereby facilitating users in carrying out their activities. Additionally, this shape is also deemed to ease its arrangement on the planning site. Because, as is known, the square shape has a character that is easy and efficient in its arrangement. Moreover, if we refer to the regulations of the Ministry of Public Works and Public Housing (PUPR) regarding earthquake-resistant building shape standards, the basic shape of the Integrated Safety Service Center building as the design object is in accordance with the earthquake-resistant building floor plan shape standard, which is a square-shaped floor plan